2007
DOI: 10.1038/sj.leu.2404968
|View full text |Cite
|
Sign up to set email alerts
|

Short telomeres and high telomerase activity in T-cell prolymphocytic leukemia

Abstract: To test the role of telomere biology in T-cell prolymphocytic leukemia (T-PLL), a rare aggressive disease characterized by the expansion of a T-cell clone derived from immuno-competent post-thymic T-lymphocytes, we analyzed telomere length and telomerase activity in subsets of peripheral blood leukocytes from 11 newly diagnosed or relapsed patients with sporadic T-PLL. Telomere length values of the leukemic T cells (mean7s.d.: 1.5370.65 kb) were all below the 1st percentile of telomere length values observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…However, CLL cells with short telomeres and high telomerase activity defined a small group of patients with a worse prognosis. Similarly, T-prolymphocytic leukaemia (T-PLL) cells have short telomeres and high telomerase activity, and T-PLL is associated with a poor prognosis [39]. Currently, telomerase inhibitors are being explored as a possible therapy for patients with T-PLL.…”
Section: Discussionmentioning
confidence: 99%
“…However, CLL cells with short telomeres and high telomerase activity defined a small group of patients with a worse prognosis. Similarly, T-prolymphocytic leukaemia (T-PLL) cells have short telomeres and high telomerase activity, and T-PLL is associated with a poor prognosis [39]. Currently, telomerase inhibitors are being explored as a possible therapy for patients with T-PLL.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study looking at 11 patients with T-cell prolymphocytic leukaemia (T-PLL), a rare and aggressive form of leukaemia, Roth et al (2007) demonstrated that the malignant T-cells have markedly shortened TL of 1AE53 kb as measured by flow-FISH. In comparison, the patients' normal T cells had a TL of 5 kb.…”
Section: T Cell Malignanciesmentioning
confidence: 99%
“…Furthermore, analysis of the T-PLL cells showed that they had markedly increased levels of TA that correlated with an increase in TERT. Finally, they were able to demonstrate that the telomerase inhibitor (BIBR1532) led to selective death of the malignant T-PLL cells in vitro (Roth et al, 2007). T-PLL therefore is a disease with both high TA and markedly low TL that would logically make the ideal target for anti-telomerase therapy.…”
Section: T Cell Malignanciesmentioning
confidence: 99%
“…Extremely short telomeres and high levels of telomerase activity have been reported in T-PLL, and T-PLL cells are sensitive to telomerase inhibition in vitro. 43 Other therapeutic targets. Other intracellular signaling pathways, such as JAK-STAT and IRF, also offer potential targets for inhibition.…”
Section: How An Understanding Of the Biology Can Help In The Developmmentioning
confidence: 99%